Hepatoportal sclerosis (obliterative portal venopathy) and nodular regenerative hyperplasia in a patient with myasthenia gravis: A case report and review of the published work. Issue 9 (15th May 2013) - Agrawal, Manasi; Rahmani, Rabin; Nakkala, Kiran; Fiel, Maria Isabel; Schiano, Thomas
Abstract : Nodular regenerative hyperplasia (NRH) and hepatoportal sclerosis, also known as obliterative portal venopathy (OPV), are two causes of non‐cirrhotic portal hypertension (NCPH). NCPH is an increasingly recognized entity that can be seen in association with collagen vascular diseases and with the use of medications such as azathioprine and didanosine, but oftentimes the etiology remains unidentified. We herein report a case of NCPH occurring due to OPV and NRH in a 64‐year‐old woman with myasthenia gravis (MG), status post‐thymectomy. Portal hypertension was diagnosed incidentally on computed tomography in the absence of predisposing factors. Extensive work‐up to determine the etiology of any underlying liver disease was unrevealing. NRH and OPV were identified on liver biopsy. Subsequently, the patient had variceal bleeding that necessitated transjugular intrahepatic portosystemic shunt placement. A few similar cases of NCPH occurring in the setting of MG have been previously reported, suggesting that the immunological mechanisms involved in the pathogenesis of myasthenia may also have contributed to the development of NCPH.